Red fluorescent ultra-small gold nanoclusters functionalized with signal molecules to probe specificity in quorum sensing receptors in gram-negative bacteria - Chahande, Anurag M.; Lathigara, Disha; Prabhune, Asmita A.; Devi, R. Nandini (Archives of Microbiology, 2021)
Ultra-small (size < 2 nm) gold nanoclusters (AuNCs) are used as fluorescent probes which have excellent applications in bioimaging and sensing due to their emission in visible and NIR spectral region. Here, this property is exploited for understanding the quorum sensing phenomenon in bacteria which is regulated by signal molecules which are specific to various species. AuNCs are then functionalized with the signal molecules, Acyl Homoserine Lactones (AHL) of varying carbon chain length, C-6, C-8, and C-12 without 3rd C modification, to sense different strains of gram-negative bacteria i.e., Escherichia coli, Cronobacter sakazakii and Pseudomonas aeruginosa. In the concentration employed, selectivity to a limited extent is observed between the three Gram-negative bacteria tested. E. coli showed emission with all the AHL conjugates and P. aeruginosa did not interact with any of the three conjugates, whereas C. sakazakii showed specificity to C-8AHL. This is probably due to selectivity for cognate AHL molecules of appropriate concentrations.
Keywords: acyl homoserine lactone; fluorescence imaging; Gold nanoclusters; quorum sensing; Receptors; selectivity